How to See the Unseen City. - Upson, S. (IEEE spectrum)
This paper presents different methods and equipments used on how to inspect underground infrastructures, networks, sewers, and pipes in some cities around the world. In New York, underground pipes are inspected using an electronic listening equipment as its first line of defense. Maintenance workers dangle a microphone down a manhole and attach it to a water main to assess whether flow has been disturbed by a leak. More detailed checks are conducted from within a pipe, using what is essentially a video camera on wheels. In pipeline lingo, such tools are quirkily known as smart pigs. In addition to capturing a digital video, a pig can perform radar and sonar scans above and below a water line, searching for indentations and holes in the walls as it rolls down in a pipe. It records its locations with odometer wheels and may be equipped with magnetic sensors to check for aberrations in metal pipes. On the other hand, Japan is the exception on the geospatial-information services front, with a national mapping repository known as ROADIC. This underground mapping system consists of utility grids layered over a road map that utilities and builders consult before breaking ground.